Language as articulate contact : toward a post-semiotic philosophy of communication - Stewart, John, 1941- (SUNY series in speech communication., 1995)
This book analyzes the prominent view that language is basically a system of signs and symbols; outlines an alternative that builds on aspects of the philosophies of Heidegger, Gadamer, Buber, and Bakhtin; and employs this alternative to criticize accounts of language developed by V.N. Volosinov, Kenneth Burke, and Calvin O. Schrag. From the perspective of communication theory, this book extends some features of the postmodern critique of representationalism to develop a post-semiotic account of the nature of language as dialogic.